Compromise agreements as a tool for judicial proceedings in Old Polish-Lithuanian Commonwealth (based on judicial materials of the Ruthenian Voivodeship in the 17th – 18th centuries) - Пуйда, Роман Богданович; Пуйда, Р. Б.; Puida, Roman B.; Завальнюк, Сергій Володимирович; Завальнюк, С. В.; Zavalniuk, Serhii V. (Drohobych : Drohobych Ivan Franko State Pedagogical University, 2025)
The purpose of the study is to clarify the role and place of compromise agreements in the judicial system of Old Polish-Lithuanian Commonwealth. The research methodology is based on the principles of scientific historicism, the use of general scientific and highly specialized historical methods. Scientific novelty consists in a comprehensive analysis of the activities of compromise courts in the territory of the Ruthenian Voivodeship of the Polish-Lithuanian Commonwealth in the 17th – 18th centuries, as an integral part of judicial proceedings. The procedural aspect of the court's activities has been reconstructed: composition, prerequisites for formation, topics of cases considered, etc. Conclusions. Compromise agreements were widely used in an everyday legal practice of the Old Polish-Lithuanian Commonwealth society as a tool for resolving conflicts. The acts of the hrodsky (magistrates') and zemstvo courts contain hundreds of references and the agreements texts, and it testifies to their importance. The participants of compromise agreements were two parties who were on equal terms. Each of them was represented by the so-called “friend”, it could be one or several people. In the 18th century the board of friends was headed by a super-arbitrator. Also in the 18th century the compromise court could use the services of vozny and other officials of local judicial and administrative institutions. Compromise agreements could be concluded between the parties who were conducting legal proceedings in the existing permanent courts. They could equally be concluded at different stages: at the beginning of legal proceedings, at the end, etc. Compromise courts covered a wide range of civil and criminal cases. Thus, they could make decisions that provided not only for material aspects, but also for imprisonment, deprivation of honour, etc.
Keywords: compromise courts; Ruthenian voivodeship; judicial proceedings of the Old Polish-Lithuanian Commonwealth; compromise agreements; mediation